Pendidikan Karakter Siswa Melalui Pembelajaran Bahasa Indonesia di Pasca Pandemi pada Madrasah Aliyah An-Najah I Karduluk, Sumenep - Albaburrahim, Albaburrahim (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Education does not only require students to have knowledge and skills. Education also aims to shape the character of students so that they have strong, critical, and moral personalities according to the noble values ​​of the Indonesian nation. Character education can be done through various lessons in class, one of which is Indonesian learning. Indonesian language learning has a great opportunity to encourage students to have characters that are in accordance with the personality values ​​of the Indonesian nation, especially in facing a pandemic. This study aims to determine the role of Indonesian language learning in instilling character education values. This study used descriptive qualitative method. Data collection techniques through documentation and observation. The analysis technique is in the form of data analysis and observation of the research object. The results of this study indicate that character education through learning Indonesian there are several personality values ​​obtained by students, namely 1) the value of honesty, 2) the value of discipline, 3) the value of responsibility, 4) the value of tolerance.